The impact of coordination training on motor skills in adolescent handball players aged 14-15 years: A randomized controlled trial - Spieszny, M.; Wasacz, W.; Kamys, Z.; Ambrozy, T.; Kasicki, K.; Kapuscinski, P.; Rydzik, L. (Baltic Journal of Health and Physical Activity, 2024)
Introduction: Motor skills are fundamental to athletic performance, particularly in sports like handball, where coordination, speed, and power are critical. This study aimed to evaluate the effects of an innovative coordination training program on the profile of motor skills of adolescent handball players compared to traditional training methods.